Upaya Resiliensi Pengrajin Tas dan Kulit Intako Tanggulangin pada Masa Pandemi dalam Kerangka Frugal Innovation - Firdayanti Hadiansyah; Achmad Room Fitrianto (Jurnal Dinamika Ekonomi & Bisnis, 2023)
The Covid-19 pandemic has had an impact on the leather craft processing industry in Tanggulangin, Sidoarjo. The limitation of all community economic activities has had an extraordinary effect on bag and leather craftsmen in the region such as decreased income, reduced workforce, which has led to business closures. Thus, this study aims to find out craftsmanship resilience efforts using frugal innovation as a solution approach amid limitations. This research used a mix of qualitative and quantitative methods with the Sustainable Livelihood Framework (SLF) analysis tool. The primary data were obtained through interview techniques and secondary data were through the Central Statistics Agency (BPS) Sidoarjo and the Sidoarjokab website. The research objects were the bag and leather craftsmen at the Tanggulangin Intako Center. The results showed that the craftsmen were identified as using 3 frugal principles as a means of resilience. The application of frugal innovation gradually helps craftsmen for resilience to regain economic prosperity after a downturn